Comparison Study of Macropollutant Removal in River Water Using Conventional Treatment and Nanofiber Membrane-Based System - Auliya Anwar; Cut Meurah Rosnelly; Ichwana Ramli; Nasrul Arahman; Afrillia Fahrina (Elkawnie, 2023)
Abstract: High levels of nitrate (NO3) and phosphate (PO4) concentrations in water sources due to agricultural drainage or municipal disposal can generate eutrophication. It is characterized by blooms of either green or blue-green algae leading to significant drops in dissolved oxygen and frequently renders many fish and zooplankton species unable to survive in the water. In this study, the efforts to reduce total suspended solids (TSS), NO3, and PO4 pollutants in river water are evaluated using conventional treatment and membrane filtration systems as a comparison. Conventional water treatment process uses bar screening, flocculation-coagulation, and settling/sedimentation to remove pollutants; while membrane filtration system rejects a wide range of pollutants using pore exclusion. This study assessed electrospinning membrane filtration made of polyacrylonitrile (PAN) and polyacrylonitrile/polyethylene glycol-silver nanoparticle (PAN/PEG-Ag). The effectiveness of removing pollutant levels after going through a conventional type of water treatment and 12% PAN membrane (EM1), and 12% PAN-PEGAg 1% (EM2) showed the reduction level of TSS was 82.76%, 75.86%, 65.52 %, NO3 reduction was 73.97%, 85.62%, 83.19%, and PO4 reduction was 77.20%, 59.60%, 53.45%. The removal efficiency using pristine PAN membrane was 81.86%, 73.02% when using the conventional process, and 64.31% when using 12% PAN-1% PEGAg. After the conventional and membrane processes, TSS and nitrate level reductions were adequate, as seen from the set quality standard values, i.e., below 50 mg/L and 10 mg/L. Meanwhile, after both water treatments, the phosphate level did not meet the water quality standard, 0.2 mg/L, as regulated in the Government Regulation Number 22 of 2021.Abstrak: Konsentrasi nitrat (NO3) dan fosfat (PO4) yang tinggi dalam sumber air karena drainase pertanian atau pembuangan kota dapat menghasilkan eutrofikasi. Hal ini ditandai dengan mekarnya ganggang hijau atau biru-hijau yang menyebabkan penurunan oksigen terlarut yang signifikan dan sering membuat banyak ikan dan spesies zooplankton tidak dapat bertahan hidup di air. Dalam studi ini, upaya untuk mengurangi polutan total padatan tersuspensi (TSS), NO3, dan PO4 dalam air sungai dievaluasi menggunakan pengolahan konvensional dan sistem filtrasi membran sebagai pembanding. Proses pengolahan air konvensional menggunakan bar screening, flokulasi-koagulasi, dan pengendapan/sedimentasi untuk menghilangkan polutan; sementara sistem filtrasi membran merejeksi berbagai macam polutan menggunakan eksklusi pori. Studi ini menilai filtrasi membran elektrospinning yang terbuat dari polyacrilonitrile (PAN) dan polyacrilonitrile/polyethylene glycol-silver nanoparticle (PAN/PEG-Ag). Efektifitas penyisihan kadar pencemar setelah melalui jenis pengolahan air secara konvensional dan membran PAN 12% (EM1), dan PAN 12%-PEGAg 1% (EM2) menunjukkan tingkat reduksi dari TSS adalah 82,76%, 75,86%, 65,52%, reduksi NO3 adalah 73,97%, 85,62%, 83,19%, dan reduksi PO4 adalah 77,20%, 59,60%, 53,45%. Efisiensi penyisihan menggunakan membran PAN murni adalah 81,86%, 73,02% bila menggunakan proses konvensional, dan 64,31% bila menggunakan 12% PAN-1% PEGAg. Setelah proses konvensional dan membran, penurunan kadar TSS dan nitrat cukup baik, terlihat dari nilai baku mutu yang ditetapkan yaitu di bawah 50 mg/L dan 10 mg/L. Sedangkan setelah dilakukan kedua pengolahan air tersebut, kadar fosfat tidak memenuhi baku mutu air yaitu 0,2 mg/L sebagaimana diatur dalam Peraturan Pemerintah Nomor 22 Tahun 2021.